PEMANFAATAN LAYANAN INFORMASI DALAM MOTIVASI BELAJAR SISWA KELAS XI IPS 2 DI SMA NEGERI 1 SIMPUR KABUPATEN HULU SUNGAI SELATAN - Rini Hardiyanti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2017)
Information Services is implemented in schools to equip students with the knowledge and understanding of the various things that are useful to know yourself, plan, and develop a pattern of life. Motivation to learn is the driving force that raises the overall learning activities, which ensures continuity of learning and giving directions and learning activities, so that the goal.This study aims to describe how the use of information services that have been given to students of SMA Negeri 1 Simpur Hulu Sungai Selatan. This type of research is qualitative research method that is based on the philosophy postpositivisme, is used to examine the condition of the natural object ..Sources of data in this research is the principal, BK teachers and students. The data collection techniques used in this research is observation, interviews, and documentaries. Analysis of the data in this research is using qualitative kind. Results from this study is an overview of how the use of information services in students' motivation in class XI IPS in SMAN 1 Simpur  Hulu Sungai Selatan after being given the service. The survey results revealed that the students make use of the information in terms of learning motivation.Based on these results, it is recommended to principals to provide oversight, provide facilities and infrastructure information services. Teachers can provide opportunities time freely so that the counselor can provide information services in the classroom. School counselors are expected to provide information services in accordance with students' needs and delivered in a way that is more interesting. Students are expected to prepare to receive and understand the importance of information services in terms of motivation to learn